Cardiovascular Risk and Hepatic Steatosis in Patients Treated at A Level 2 Hospital - Cervantes-Suarez A; Briones-Pérez I; Fernandez-Flores E (International Journal of Medical Science and Clinical Research Studies, 2026)
Background: Hepatic steatosis, currently recognized as a metabolic liver disease, is linked to the global epidemic of obesity, insulin resistance, type 2 diabetes, metabolic syndrome, and cardiovascular disorders. Cardiovascular disease is the leading cause of death worldwide. From a pathophysiological perspective, the accumulation of intrahepatic lipids is associated with chronic low-grade inflammation, oxidative stress, endothelial dysfunction, and activation for the development of atherosclerosis. These alterations result in an increased risk of ischemic heart disease and cardiovascular disease. Imaging plays a role in the non-invasive detection of hepatic steatosis in its different stages using abdominal ultrasound and in the evaluation of cardiovascular risk markers using cardiac computed tomography, as well as in the identification of atherosclerotic calcifications of the coronary arteries. General objective: To determine the association between cardiovascular risk and the degree of hepatic steatosis in patients treated at HGRO No 1. Material and methods: This is a cross-sectional, observational, prospective, and analytical study. Non-random quota sampling was used. Frequencies and percentages were obtained for qualitative variables, and measures of central tendency and dispersion were obtained for quantitative variables. The chi- square test was used for inferential statistics , achieving statistical significance with a p-value